Managing Spent Nuclear Fuel Strategy Alternatives and Policy Implications - LaTourrette, Tom (RAND Corporation, 2010)
Nuclear power is receiving renewed interest because of its low greenhouse gas emissions. However, if nuclear power is to be sustainable option for the United States, methods for managing spent fuel that meet stringent safety and environmental standards must be implemented. This report examines technical and institutional approaches to spent fuel management and highlights policy implications of pursuing alternative strategies.